Attitudes of Local Population Towards the Impacts of Tourism Development: Evidence From Czechia - Linderová, Ivica; Scholz, Petr; Almeida, Nuno (Frontiers in Psychology, 2021)
Increasing the socio-economic effects caused by the tourism development in the local population, they adopt some attitudes according to the impacts directly or indirectly perceived. However, some of this impact can be considered positive or negative, according to different perspectives. The issue of the resident-tourist relationship has been much-discussed recently. Therefore, many case studies are being conducted that address the impacts on both residents and tourists. The goal of this manuscript is to analyze the attitudes of local residents to the development of tourism in the urban monument zone Předhradí. Primary data were collected in a questionnaire survey for residents who have a permanent residence in a municipality of Předhradí in 2020. In our research, we tried to identify the significant negative impacts of tourism development. In the same way, we evaluate how the locals see positive effects on their quality of life conducted with tourism development. The research finds out that local respondents perceived some negative impacts to increase the economic perspective, as they referred to in the higher traffic load or increased noise. The pandemic crises are perceived as a game-changer in the tourism industry. For that reason, we suggest the primary considerations for future research not only with the academic perfective as for the practical point of view. The local population's entrepreneurship attitudes must be one of the tools to assume the resilience toward the tourism development impacts.